Experiencing teaching with babies in supervised practice: organizing spaces, play and interactions - Eloisa Acires Candal Rocha; Lívia Rezende Girardi; Márcia Buss Simão (Universidade Federal de Santa Catarina, 2014)
This text aims to present reflections on the experience Supervised Internship in Early Childhood Education in the School of Education of the Federal University of Santa Catarina. The stage was developed in a nursery of Municipal Florianópolis, located in Morro Penitentiary in group one (G1), consisting of 15 infants, nine girls and six boys ranging in age from eight months to one year and three months. The propositions in shared teaching had centered on the organization of space and time as elements that could contribute to the constitution of the self and recognizing the other through interactions and games. Initially we present the conception of the child and childhood that permeated the teaching practice in the stage of early childhood education, later addressed the importance of having an attentive and sensitive eye to realize that babies show to make propositions. Finally, reflections on the propositions made about the organization of space and time as elements that contribute to the expansion of interactions and repertoires of play of babies are delivered.